EKSPLORASI EFEKTIVITAS EDUKASI GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) TERHADAP PERUBAHAN GAYA HIDUP MASYARAKAT DI KELURAHAN JATIBARU KOTA BIMA - Bambang Irawan (Akademi Kebidanan Harapan Bunda Bima, 2026)
The Healthy Living Community Movement (GERMAS) is a national health promotion program designed to improve public awareness and encourage healthy lifestyles through promotive and preventive approaches. The effectiveness of GERMAS depends largely on the quality of health education delivered to the community. Objective: This study aimed to explore the effectiveness of GERMAS education in changing the lifestyle of residents in Jatibaru Village, Bima City. Methods: A qualitative phenomenological approach was employed. Fifteen participants consisting of health workers, community health volunteers, community leaders, and residents were selected purposively. Data were collected through in-depth interviews, observation, and documentation. Data analysis followed the Miles and Huberman interactive model. Results: Five major themes emerged: increased knowledge regarding GERMAS, improved healthy lifestyle practices, greater awareness of routine health examinations, barriers to behavioral change, and supporting factors including family support, community participation, and local government commitment. Conclusion: GERMAS education contributes positively to lifestyle changes among community members. Continuous education and community empowerment are essential to maintain sustainable healthy behavior.